Many important group-level traits are institutions. Issue 3 (27th June 2014) - Zefferman, Matthew R.; Richerson, Peter J.
Abstract: Smaldino makes a solid contribution to the literature on the evolution of human social organization by pointing out that group-level-traits (GLTs) often emerge from the interactions of group members in such a way that their effects are not easily partitioned into individual selection. However, we argue that he too readily dismisses institutional analysis as a tool for understanding these traits.